PROSPECTS OF DEVELOPMENT OF BLOCKCHAIN TECHNOLOGY IN RUSSIA: COMPETITIVE ADVANTAGES AND BARRIERS - L. A. Tsvetkova (Ekonomika Nauki)
The analysis of prospects of introduction of the developments related to blokcheyn in the world and in Russia has been made. Key investors and beneficiaries in the development of blockchain technologies were identified. High competitiveness of Russian developments, unique staffing, and favorable climatic conditions for the development of blockade technologies in the Russian Federation were noted. The patent activity in the world has been analyzed and the place of Russia on the patent landscape in the field of blockchain technologies has been determined. It is shown that, to date, the weak position of Russian developers in the global patent landscape in the field of blockchain is not critical due to the high level of uncertainty in matters of protectability of the proposed blockchain algorithms. Special attention was paid to the delayed, perhaps shortterm, readiness of residents of industrially developed countries to expand in the global space of intellectual property associated with the blockchain as soon as the patentability of the proposed solutions is proved. It is concluded that the next 2–3 years should be considered as a “window of opportunity” to form the prerequisites for Russia’s technological leadership in the cluster of block-technologies.